Struktur Semantis Verba Kiru ‘Potong’: Kajian Metabahasa Semantik Alami - Dewi, Sifta Sari; Mulyadi, Mulyadi; Pujiono, Mhd (Universitas Diponegoro, 2019)
(Title: Semantic Structures Of Kiru ‘Cut’ Verbs) This study aims to analyze the categorization and meaning of the kiru